2012
DOI: 10.1007/s11105-012-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis

Abstract: Plant lipoxygenases (LOXs) are functionally diverse class of dioxygenases involved in multiple physiological processes such as plant growth, biotic and abiotic stress responses, and secondary metabolite accumulation. In this paper, two LOX genes, TcLOX1 and TcLOX2, were cloned from Taxus chinensis cells. Multiple alignment of the deduced amino acid sequences with those of other plants demonstrated the putative LH2/PLAT domain, lipoxygenase iron-binding catalytic domain, lipoxygenase_1 and lipoxygenase_2 signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, the 9-LOXs had V/H/L in the corresponding position instead ( Figure S2). The conserved V residue associated with 9-LOX activity is a characteristic of LOX enzymes, while some 9-LOXs possess no V residue at the position [37][38][39]. In addition, the analysis of conserved motif distribution and exon-intron arrangement further supported the phylogenetic results.…”
Section: Discussionmentioning
confidence: 55%
“…However, the 9-LOXs had V/H/L in the corresponding position instead ( Figure S2). The conserved V residue associated with 9-LOX activity is a characteristic of LOX enzymes, while some 9-LOXs possess no V residue at the position [37][38][39]. In addition, the analysis of conserved motif distribution and exon-intron arrangement further supported the phylogenetic results.…”
Section: Discussionmentioning
confidence: 55%
“…LOX activity has been positively correlated with paclitaxel accumulation in elicited T. chinensis cells (Huang et al 2005;Wang and Wu 2005). Moreover, Li et al (2012) observed strong up-regulation of the TcLOX1 LOX gene, cloned from T. chinensis cells and preferentially expressed in stems and roots, in response to MJ elicitation.…”
Section: Taxane Production and Pal Activitymentioning
confidence: 86%
“…In the present study a bifunctional inhibitor/lipid-transfer protein/seed storage 2S albumin superfamily protein (Dir1) [56] and PLAT/LH2 domain-containing lipoxygenase have been upregulated not only under osmotic stress, but after PUT pre-treatment, while the highest induction was found after PUT pre-treated + PEG treatment. The PLAT/LH2 domain-containing lipoxygenase also has a role in plant signalling, as it was reported to be induced by ABA, SA, jasmonate or wounding [57].…”
Section: Discussionmentioning
confidence: 99%